(untitled) (Clinics, 2012)
OBJECTIVE: Celiac disease is a permanent enteropathy caused by the ingestion of gluten, which leads to an immunemediated inflammation of the small intestine mucosa. The prevalence of celiac disease varies among different nations and ethnic backgrounds, and its diversity is determined by genetic and environmental factors. São Paulo city is one of the largest cities in the world, with a vast population and an important history of internal migratory flow from other Brazilian regions, as well as immigration from other, primarily European, countries, resulting in significant miscegenation. The aim of the present study was to estimate the prevalence of adults with undiagnosed celiac disease among blood donors of São Paulo by collecting information on the ancestry of the population studied. METHODS: The prevalence of celiac disease was assessed by screening for positive IgA transglutaminase and IgA endomysium antibodies in 4,000 donors (volunteers) in the Fundação Pró-Sangue Blood Center of São Paulo, São Paulo, Brazil. The antibody-positive subjects were asked to undergo a small bowel biopsy. RESULTS: Of the 4,000 subjects, twenty-four had positive tests, although both antibody tests were not always concordant. For example, ten subjects were positive for IgA tissue transglutaminase only. In twenty-one positive patients, duodenal biopsies were performed, and the diagnosis of celiac disease was confirmed in fourteen patients (Marsh criteria modified by Oberhuber). In this group, 67% claimed to have European ancestry, mainly from Italy, Portugal and Spain. CONCLUSION: The prevalence of celiac disease is at least 1:286 among supposedly healthy blood bank volunteers in São Paulo, Brazil.